Avaliação do estado nutricional de mudas de Gonçalo Alves (Astronium Fraxinifolium) - Mizobata, Kellian Kenji Gonzaga da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The planting of seedlings, the establishment and maintenance of the natural regeneration process, or the combination thereof, are methods used in the recovery of degraded or disturbed environments, however, often require the addition of soil conditioners. This study aimed to evaluate the influence of conditioners, introduced in degraded soil on growth and nutritional status of Astronium fraxinifolium seedlings. To conduct the experimentation were used as degraded soil conditioner, ash from sugarcane bagasse (CZ) and macrophytes (MC), at the doses of 0, 15, 30 and 45 t ha-1 and 0, 16 and 32 t ha-1 respectively, which combined produced 12 treatments, with three replications, and for field installation, was used the experimental randomized block design. Astronium fraxinifolium (Gonçalo Alves) seedlings, native tree species in cerrado, were introduced in the experimental area and, after 12 months, were evaluated for leaf concentration of nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, boron, copper, iron, manganese and zinc (N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn, respectively). Seedlings and adult plants of A. fraxinifolium were collected in preserved cerrado reserve were also analyzed for nutrients foliar concentration to perform a comparative analysis. The leaves collection in the preserved cerrado and experimental area, was accompanied by soil sampling (0.0 - 0,20 m deep), which was analyzed for phosphorus, OM (organic matter), pH, K, Ca, Mg, Al+H (potential acidity), Al (aluminum), Cu, Fe, Mn and Zn. The results show that the applied residues contributed to raise the foliar concentration of Cu and Fe. The foliar concentration of nutrients was higher in A. fraxinifolium seedlings from preserved cerrado, except for B, which was similar between areas, besides Cu and Fe with higher levels in the seedlings from experimental area. The combined addition of residues (MC and CZ), led to increase the plants height and diameter. This...

O plantio de mudas, o estabelecimento e a manutenção do processo de regeneração natural, ou a combinação destes, são métodos utilizados na recuperação de ambientes degradados ou perturbados, no entanto, muitas vezes demandam a introdução de condicionantes ao solo. Este trabalho teve por objetivos avaliar a influencia de condicionantes, introduzidos em solo degradado, sobre o crescimento e o estado nutricional de mudas de Astronium fraxinifolium. Para isto, utilizaram-se, como condicionantes do solo degradado, cinza do bagaço da cana-de-açúcar (CZ) e macrófitas aquáticas (MC), nas doses 0, 15, 30 e 45 t ha-1 e 0, 16 e 32 t ha-1 respectivamente, que combinadas, geraram 12 tratamentos, com três repetições, utilizando, para instalação em campo, o delineamento experimental em blocos casualizados. Mudas de Astronium fraxinifolium (Gonçalo Alves), espécie arbórea nativa do cerrado, foram introduzidas na área experimental e, após 12 meses, foram avaliadas quanto à concentração foliar de nitrogênio, fósforo, potássio, cálcio, magnésio, enxofre, boro, cobre, ferro, manganês e zinco (N, P, K, Ca, Mg, S, B, Cu, Fe, Mn e Zn, respectivamente). Mudas e plantas adultas de A. fraxinifolium, coletadas em reserva de cerrado conservado também foram analisadas quanto à concentração de nutrientes foliares, para realização de uma analise comparativa. A coleta de folhas no cerrado conservado e na área experimental, foi acompanhada de coleta de solo (0,0 -0,20m de profundidade), o qual foi analisado para os teores de P, MO (matéria orgânica), pH, K, Ca, Mg, H+Al (acidez potencial), Al (alumínio), Cu, Fe, Mn e Zn. Os resultados mostram que os resíduos aplicados contribuíram para elevar a concentração de Cu e Fe foliar. A concentração foliar dos nutrientes avaliados foram superiores nas mudas de A. fraxinifolium do cerrado conservado, exceto B, semelhante entre as áreas e Cu e Fe com teores mais elevados nas mudas da...
Keywords: Solos - Fertilidade; Degradação ambiental; Cerrados